Formação humana e musical através do Canto Coral: um estudo de caso no Coral da UFC - Moraes, Davi Silvino (2015)
The reality of Fortaleza’s public schools do not offer collective musical practices in their curriculum, making the Choral an informal space of human and musical education through aesthetic experiences provided by the collective singing, even for people with adjustment singing problems. Therefore this research aims to identify the musical and human educational practices developed by educator conductor within the choir practice. Researched Moraes (1993, 2007), Zander (2008), Mathias (1986), Matos (2008), Garretson (1998), Amato (2007), Figueiredo (1999.2006), Kerr (2006), Sobreira (2002, 2003), Bellochio (2008), Forcussi (1985) among others, the theoretical foundation for this work. With interest in the study of vocal and musical preparation process will develop a qualitative research focused on a case study in ADUFC’s Choral which holds the relevant characteristics for the current research. It was identified practices of human development taking place in conjunction with musical training practices permeating moments of vocal and body preparation with the use of harmonic instrument (guitar and keyboard), music education linked to the memory of a selected repertoire from a didactic proposal and methodological practices to overcome tuning problems. It was noted that the test, as well as in the studied choral performance, was used as a music teaching environment and exercise human values through personal and interpersonal interaction intense overshoot.